Persepsi Siswa Terhadap LKS Terintegrasi Islam Untuk Materi KPK Dan FPB - Mike Riyanti; Ummi Khoiroh; Yennita Yennita; M. Imamuddin (Universitas Pahlawan Tuanku Tambusai, 2024)
Islamic Integrated mathematics learning is aan education approach that involves Islamic values in mathematics materials to provide useful learning experiences to students. This study aims to desceibe students’ perceptions of Islamic Integration Student Worksheets on KPK & FPB material. The type of research used is descriptive with a quantitative approach. This research method is a survey using a questionnaire instrument. The variable in this study is the perception of grade V students at SDN 23 KUBANG PUTIH towards the Islamic Integration Student Worksheet. The population in this study included all grade V students at SDN 23 KUBANG PUTIH, totaling 22 students. The technique used in sampling is by using Purposive sampling technique. The result showed that students’ perceptions of the Islamic Integration LKS KPK & FPB material obtained most students strongly agree that this Islamic Integrated based LKS really helps students in understanding learning and remembering the concepts of learning concepts and can add Islamic insight for students so that students feel more interested in Islamic integrated based LKS, this is in accordance with the percentage obtained from the questionnaire that been given to students .